Stanowisko Komisji Europejskiej oraz rządów państw członkowskich Unii Europejskiej wobec reformy ustrojowej Unii Gospodarczej i Walutowej (2017-2022) - Węc, Janusz J. (Studia Polityczne, 2023)
This article aims to analyse the positions of the European Commission (EC) and the governments of the EU Member States regarding the system reform of the Economic and Monetary Union (EMU). This analysis leads the author to the following conclusions. First, the EC has consistently advocated the creation of three new structures within the existing EMU by the end of 2025 (i.e. the Financial Union, the Fiscal Union and the Economic Union) and a radical extension of the powers of the EU institutions in the financial, fiscal and economic policies of the Member States. On the other hand, some EU Member State governments, notably Germany, Austria, the Netherlands, Denmark and Sweden, were opposed not only to such far-reaching system reform, but also to the pace of its implementation. All the draft laws of the EC went much further than the proposals of the Eurozone Summit or the Eurogroup in terms of system change. Thirdly, the attitude of the Eurozone Member States themselves towards the reform examined was not uniform. While the southern eurozone countries, led by France and Italy, believed that financial solidarity within the eurozone should be understood in the broadest sense, the northern eurozone countries, led by Germany, opposed it. As a result, the differences of opinion between the EU Member States were compounded by controversies between the Eurozone countries, which further complicated the process of reforming the EMU system. Fourthly, the reorientation of the stance of the governments of Germany, Austria, the Netherlands, Denmark and Sweden towards a communitisation of debt in 2020 and 2021, illustrated by the example of the Reconstruction Fund, did not pave the way for resolving the long-standing dispute over the establishment of a European deposit guarantee scheme.